2022
DOI: 10.3389/fendo.2021.824078
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Critical Analysis on Dietary Supplements for Male Infertility: From a Blend of Ingredients to a Rationale Strategy

Abstract: ContentDietary supplements (DS) for male infertility marketed in Italy were evaluated for composition, concentration of ingredients, and recommended daily dose. A systematic review of literature identified ingredients potentially effective on sperm parameters and their minimal effective daily dose (mED).ObjectiveThis study was conducted in order to critically evaluate the composition and efficacy of DS marketed in Italy.Design, Setting, and ParticipantsThis was a systematic review of randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Therefore, nutrition is recognized to affect sperm quality through several mechanisms. As an example, the supply of essential nutrients such as zinc, selenium, essential fatty acids, folic acid, and vitamin B12 is recognized to be important in the maturation of spermatozoa [44]. In addition, weight status, the influence of physiological mechanisms involved in spermatogenesis (hormonal modulation and red-ox balance), and the physiology of the accessory glands, are strongly linked to sperm quality [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nutrition is recognized to affect sperm quality through several mechanisms. As an example, the supply of essential nutrients such as zinc, selenium, essential fatty acids, folic acid, and vitamin B12 is recognized to be important in the maturation of spermatozoa [44]. In addition, weight status, the influence of physiological mechanisms involved in spermatogenesis (hormonal modulation and red-ox balance), and the physiology of the accessory glands, are strongly linked to sperm quality [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In recent systematic reviews by our group on DS formulation for male and female infertility [14,15], we suggested a formula to evaluate the expected efficacy of a DS based on the whole composition, specifically, each formulation was evaluated in relation to the fact that if each single active ingredient was considered an EI, and whether each one reached at least the mED based on the suggested daily dose of intake. The equation was evaluated using an adapted version of the validated scoring system that The American Heart Association has developed for analyzing scientific evidence from clinical trials [16].…”
Section: Definition Of Potential Active Ingredients Minimal Effective...mentioning
confidence: 99%
“…Therefore, antioxidant therapies have been explored to reduce the damage of oxidative stress on male fertility [19][20][21][22][23][24][25]. The systematic review and meta-analysis study of Garolla reported that Dietary supplements for male infertility have potential efficacy in improving sperm parameters and DNA integrity even though many supplements have uncertain effects [26]. Scaruffi et al, in 2021, indicated that administering antioxidant treatment to men with low fertilization rates in their previous intracytoplasmic sperm injection (ICSI) cycles could potentially have a positive impact on the reproductive potential of their sperm [27].…”
Section: Introductionmentioning
confidence: 99%